MENINGKATKAN KINERJA UKM BATIK PADA PENGUSAHA MUSLIMAH - Iqbal Arraniri; Dewi Putri Anjar Wulan (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to examine the effect of entrepreneurial orientation and organizational learning on the quality of strategic assets, and also the effect of the quality of strategic assets on business performance. This research was conducted at UKM Batik Semarang, the respondents used were 102 respondents. The data was processed using Structural Equation Modeling (SEM) with the help of the Analysis of Moment Structure (AMOS) version 23.0 program. Based on the results of the analysis, it is concluded that the effect of entrepreneurial orientation on strategic asset quality shows a CR value of -0.338 and with a probability of 0.735, testing the effect of entrepreneurial orientation on business performance shows a CR value of 2.499 and with a probability of 0.012, testing organizational learning on strategic asset quality shows a CR is 4.881 and with a probability of 0.001., testing the effect of organizational learning on business performance shows a CR value of 1.351 and with a probability of 0.177, the effect of strategic asset quality on business performance shows a CR value of 2.067 and a probability of 0.039.